Julio Cortázar at Teachers College «Mariano Acosta». Biographical traits in his education - Ayuso, María Luz; Pineau, Pablo Luis (Historia y Memoria de la Educación, 2018)
From an investigation in the historical archive «Armenia Euredgian» of the Normal School N.º 2 «Mariano Acosta» in the City of Buenos Aires, we present three versions of the relationship between the writer Julio Cortázar and the school where he was trained as a teacher during the 1930s. Our starting hypothesis is that the history of an institution must be understood in the double framework offered by the history of education and the general history of the country. By examining how the history of the school was intertwined with the history of education and of the country, we hope to reveal certain clues about the different configurations of school culture produced by the individuals who inhabited the school. The first of these versions refers to the most explicit position of the author, who denounces the formation received as that of «a machine of fascists». The Normal School, which by this time was officially recognized as an element of cultural irradiation, was extolled and respected in its role of training citizens for the Republic; it is described by Cortázar as «an immense lie». Through his images, he denounces the non-fulfillment of the function of the educative system in the formation of educated citizens and men. The second version of the school is mounted on the first, and tends towards a dreamlike and sinister portrayal, represented mainly through the story «The school at night». In Cortázar’s own words, these are «imaginary facts that have been written as a symbolic equivalent of reality». In his story, he invites us to believe that in the supposed normality of the «Normal School» dark ghosts are hidden, in the context of a period which saw the advancement of authoritarian positions in the country and in their education. Finally, a third version affords us a view of a school where individuals rebel against the models proposed in previous versions and inscribe them in more democratic political, cultural and pedagogical traditions. This interpretation is evidenced mainly through the concrete ways in which Cortázar lived in the school in his student years, and more specifically as director of the magazine Addenda, publication of the Student Association.